Navigating Media Ambivalence: Strategies of Resistance, Avoidance, and Engagement with Media Technology in Everyday Life - Rosenthal, Michele; Ribak, Rivka; Liberman, Rachael; Echchaibi, Nabil; Portwood-Stacer, Laura (AoIR Selected Papers of Internet Research, 2013)
As media technologies continue to infiltrate the domestic sphere with interactive opportunities, an increased interest in time and content management has surfaced. Social media websites such as Facebook and Twitter have been commonly associated with “wasted time” and the accessibility of unchecked content has placed a strain on the preservation of family ethics and values. On the other hand, media technologies continue to offer spaces of both meaningful and necessary communication, as well as enjoyment, education, creativity, and political action. Based on this cultural conundrum, important questions about social practice and media resistance follow: Under what logics are individuals and families using deciding to resist media technologies? What are the everyday practices of media ambivalence and resistance and how do they operate in the domestic sphere? In most research and popular discussion of media texts and platforms, the focus is understandably on current or potential users of media. This panel aims to provide space for discussing an important, though perhaps under-attended to, phenomenon within media consumption: the active non-use or negotiation of media by subjects who hold ambivalent attitudes toward communication technologies. Using empirical evidence and discourse analysis, each of the papers on this panel draws attention to the strategies employed by people who want to actively manage their own media use, as well as that of their families. The papers collected here consider a variety of communication technologies (email, television, smart phones, and social network sites) and focus on a range of factors (including gender, religion, and national context) that shape the attitudes taken and the tactics deployed in regulating media use. The first paper in this panel explores and analyzes technological and discursive “tactics” (i.e., “screen time”) that users employ to negotiate and limit media use for themselves and their families. Drawing upon qualitative interviews conducted in households in Israel, the authors try to make sense of these different practices through comparisons with research conducted about parents and children. The second paper looks at the role of gender, as a social practice, in the regulation of domestic media consumption—including the gender identification of the primary policing parent and resistance toward gendered symbols in media culture—in order to identify how gender norms are perpetuated through practices of media regulation. The third paper in this panel explores how Muslims in the United States devise evasive tactics that both engage and resist the proliferation of media technologies in the household. In particular, the author argues that given their media deficit in American society, Muslims often feel they cannot afford to resist media technologies, particularly smart phones and social media because of their connective qualities and their interventionist affordances. Finally, the last paper examines the practice of refusal of social media platforms, for example, the active resistance by potential users to participation on sites like Facebook. The author argues that this works against the potential for media refusal to function as effective strategy of collective action. Practices of social media refusal and the discourses around it serve as sites of symbolic and material struggle within the contemporary commercial media context. As a panel, the papers converse with each other to examine the ways that individuals and families confront their usage of new technologies in a media saturated age. In particular, the nuances of media resistance are analyzed at the discursive and textual level in order to understand the productive ways in which media technology is managed. In an age where individuals and families increasingly use technology to restrict their technology use, scholarship on media ambivalence becomes essential to understanding the contemporary media landscape.